Research advances in the integration of big data and smart computing - Mallick, Pradeep Kumar, 1984- (Hershey, PA : Information Science Reference, an imprint of IGI Global, 2016)
'This book builds on the available literature in the realm of Big Data while providing further research opportunities in this dynamic field to help readers to adopt and implement new paradigms in computational methods across the globe'--
Includes bibliographical references and index.
Keywords: Big data